Re-Visiting Angela Carter
XIV, 207 p.
Keywords: Focusing on questions of intertextuality, authorship and representation, this book offers a re-examination of one of the twentieth century's most important British writers. A provocative collection both offers new readings of Carter's opus, and contributes to contemporary critical debates concerning gender, postmodernism and intertextual theory.